Teknik Komunikasi Persuasif Ikatan Pelajar Al-Washliyah dalam Meningkatkan Ibadah Sholat bagi para Pelajar Madrasah Aliyah Al Washliyah Swasta Kecamatan Kualuh Hulu Kab. Labuhan Batu Utara - Yusup Ardiansyah; Efi Brata Madya; Khatibah Khatibah (Maktabatun: Jurnal Perpustakaan dan Informasi, 2023)
This research aims to get a real picture of the implementation of persuasive communication by the Al Washliyah Student Association in improving the quality of prayer services for Al Washliyah Private Madrasah Aliyah students, Kualuh Hulu district, North Labuhan Batu district, seen from the persuasive communication techniques used by the Al Washliyah Student Association in the communication process. to private Madrasah Aliyah Al Washliyah students and the application of persuasive communication techniques. This research is descriptive research with a qualitative approach. The research subject is the al Washliyah student association consisting of the chairman, secretary and members. Data collection techniques include observation, interviews. The analysis technique used in this research is a descriptive analysis model which consists of data collection, organizing data, data management, data verification and interpretation, conclusions. ` Then the data validity technique used is method and source triangulation technique. Based on the research that has been carried out, the results obtained are: 1) The persuasive communication techniques used by the Al Washliyah Student Association in improving prayer services for Madrasah Aliyah Al Washliyah students are association techniques, integration techniques, arrangement techniques, and red herring techniques. 2) the application of persuasive communication techniques is successfully carried out through planned programs such as routine recitation programs, cadre formation programs.